Theatre spaces 1920-2020 finding the fun in functionalism - Mackintosh, Iain 1937- (Methuen drama, Bloomsbury, 2023)
"In this hands-on account of the creation of new theatre spaces spanning a century, Iain Mackintosh offers a compelling history that is part memoir, part impassioned call to rethink the design of our theatre spaces and the future of live theatre. As the originator of theatre designs as diverse as the Cottesloe in 1977, Glyndebourne in 1994 and the Orange Tree Theatre in 1991, he discovered why the shows worked in some theatres and did not in others. It is this unique blend of expertise and experience that informs this riveting account of the creation of many of the best-known theatre spaces in Britain, besides many international examples"
Keywords: Geschichte 1920-2020; Theaterbau; Großbritannien